Enhancing Î±-Amylase and Cellulase in vivo Enzyme Expressions on Sago Pith Residue Using Bacilllus amyloliquefaciens UMAS 1002 - Faisal Ali, Anwarali Khan; Awang Ahmad Sallehin, Awang Husaini (Asian Network for Scientific network, 2006)
The effect of Solid State Fermentation (SSF) parameters on the production of extracellular Î±-amylase and cellulase (endoglucanases) by Bacillus amyloliquefaciens UMAS 1002 using sago pith residue hampas in shaker flasks was investigated in this study. The appropriate incubation period, temperature, pH, agitation speed, inoculum concentration, hampas concentration and additive substrate effect were optimized for enzyme production. The activity of Î±-amylase and cellulase was at 14.19 and 13.15 IU mL -1 , respectively in optimal culture medium. Maximum yield for both enzymes were achieved by employing 4% w/v hampas in 0.2 M citrate buffer at pH 6 and incubated at 40Â°C for 6 h with agitation speed of 100 rpm. Inoculum concentrations were found to be optimum at 3% v/v and 4% v/v for Î±-amylase and cellulase, respectively. Enzyme activity was 2.8 (10.80 IU mL -1 ) and 3.2 (9.38 IU mL -1 ) fold higher for Î±-amylase and cellulase respectively when 1% w/v soluble starch was applied as additive substrates with 0.5% hampas. However in optimal media that consist of 4%w/v of hampas, addition of 1% w/v soluble starch intend to inhibit both enzyme productions. Result revealed that temperature, pH and shaking condition were the most significant factors for the production of Î±-amylase and cellulase enzyme. Temperature influenced enzyme production by affecting the other parameters including bacterial growth, pH, Dissolved Oxygen (DO) and reducing sugars. Nevertheless, shaking condition could affect DO concentration that in turn affected bacterial growth and enzymes production too